2019
DOI: 10.1101/562553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative Mass Spectrometry Imaging Reveals Mutation Status-independent Lack of Imatinib Penetration into Liver Metastases of Gastrointestinal Stromal Tumors

Abstract: Mass spectrometry imaging (MSI) is an enabling technology for label-free drug disposition studies at high spatial resolution in life science-and pharmaceutical research. We present the first extensive clinical matrix-assisted laser desorption/ionization (MALDI) quantitative mass spectrometry imaging (qMSI) study of drug uptake and distribution in clinical specimen, analyzing 56 specimens of tumor and corresponding non-tumor tissues from 28 imatinib-treated patients with biopsy-proven gastrointestinal stromal t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…MSI data suggest that unequal or insufficient drug distribution within tumors may contribute to treatment failure (Figure 2). It was shown that the receptor tyrosine kinase inhibitor imatinib was not detected in liver metastases, although the adjacent tissue was saturated with the drug [58]. Similarly, while the pancreatic cancer treatment Gemcitabine, and in particular its active metabolites were detected throughout tumors, other small molecules such as the ATR inhibitor (AZD6738) was only detected in the surrounding non-cancerous tissue [59].…”
Section: Information Of Metabolic Interaction Of the Tumor With The T...mentioning
confidence: 99%
See 1 more Smart Citation
“…MSI data suggest that unequal or insufficient drug distribution within tumors may contribute to treatment failure (Figure 2). It was shown that the receptor tyrosine kinase inhibitor imatinib was not detected in liver metastases, although the adjacent tissue was saturated with the drug [58]. Similarly, while the pancreatic cancer treatment Gemcitabine, and in particular its active metabolites were detected throughout tumors, other small molecules such as the ATR inhibitor (AZD6738) was only detected in the surrounding non-cancerous tissue [59].…”
Section: Information Of Metabolic Interaction Of the Tumor With The T...mentioning
confidence: 99%
“…In the panel of drug distribution, the top image shows the distribution of AZD6738 and Gemcitabine (GEM) between pancreatic ductal adenocarcinoma (PDAC) and pancreatic tissue [59] On the middle panel is represents the preferred localization of Paclitaxel (PTX) on the margins of a malignant pleural mesothelioma [61]. On the bottom image the absence of imatinib in liver metastasis is visualized by MSI [58]. On the metabolic interactions panel, gliomas with IDH mutations showed a regional distribution of D-2-HG that inversely correlated with the detection of CD8 + T-cells [56].…”
Section: Figure 2 Application Of Mass Spectrometry Imaging (Msi)mentioning
confidence: 99%
“…36 In such approaches, a suitable IS (again typically a SIL analogue of the compound of interest) is sprayed evenly across a tissue sample, and the endogenous signal is normalised to the IS signal in each pixel. Q-MSI has most been most widely in the pharmacological context for drug imaging, including imatinib, 37 clozapine, 38 and rifampicin, 39 among others. 40 In pharmacokinetic/pharmacodynamics (PK/PD) studies, knowing the spatial distribution of pharmaceutical compounds and their localised concentrations is key to a deeper understanding of drug-target engagement, metabolism, biomarker response, changes in the tumour microenvironment and/or resolution of tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments have also expanded the capabilities of quantifying analytes of interest in situ (Vismeh et al, 2012;Pirman et al, 2013;Swales et al, 2018;Sammour et al, 2019;Handler et al, 2021). The continuous advancements of MSI, including the high sensitivity and specificity of analyte detection as well as the increasing spatial resolution, have rapidly progressed the technique in drug development and has gained a credible reputation within the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%